Unpacking Mrs Wood's suitcases : the signifying potential of unsewn cloth : a thesis presented in partial fulfilment of the requirement for the degree of Master of Philosophy at Massey University, Wellington, New Zealand - Mutsaers, Lilian (Massey University, 2009)
This thesis examines unsewn cloth pieces which once belonged to Victoria Wood and places them into their social and historical context. It uses the biography of Victoria Wood and her fabrics to argue for the importance of fabric collecting and dressmaking for New Zealand women from 1935 to 1955. It questions why ubiquitous fabrics bought for dress making are not represented in historical accounts of women, or in more general accounts of historical clothing and dress. Aspects of material culture theories are employed to analyse the material properties of the fabric pieces. These are situated within a wider domestic context to demonstrate that there were intrinsic qualities of fabric that influenced and were imagined by many women in this period. Oral histories and other documentary research add to the wider account and provide evidence of the way that dressmaking fabrics reflected the shifting notions of domesticity. The thesis suggests that fabrics bought for the creation of clothing can represent the past or a person. It also demonstrates how dressmaking fabrics simultaneously embody personal and social narratives which reflect the emotional and cultural values of a particular period. In this thesis I construct narratives which are based on the social and historical findings to highlight the importance of fabric collecting and dressmaking as an everyday domestic practice.
Keywords: Fabric; Dressmaking; Fields of Research::370000 Studies in Human Society::370300 Anthropology::370302 Social and cultural anthropology